THE CATALOGUE OF FUNDAMENTAL CHARACTERISTICS OF COOL GIANT STARS - Komarov, N. S.; Dragunova, A. V.; Korotina, L. V.; Shevchuk, T. V. (Одеські астрономічні публікації, 2017)
The characteristics - V, Sp, Teff, lg g, Fe/H, r, Mv, Mbol, L/Lsun, R/Rsun, M/Msun of 975 cool giant stars are given as a catalogue. The main results of using a data of catalogue are adduced